Chemical conjugation of FITC to track silica nanoparticles in vivo and in vitro: An emerging method to assess the reproductive toxicity of industrial nanomaterials. (July 2021) - Li, Junxia; Tian, Jiaqi; Yin, Haoyu; Peng, Yanjie; Liu, Song; Yao, Sanqiao; Zhang, Lin
Graphical abstract: Highlights: FITC was successfully coupled onto SiNPs based on the Stöber method. SiNP penetrated the trophoblast membrane and induced biological dysfunction in vitro . Uterine accumulation of SiNP triggered acute inflammation in vivo . SiNP-induced reproductive toxicity was mediated by the PPARγ signaling pathway. Abstract: Previous studies have demonstrated that silica nanoparticle (SiNP) exposure induces pulmonary and cardiovascular diseases, yet their transportation and degradation in vivo have not been fully elucidated. From the perspective of reproduction, this study was implemented to examine the uterine accumulation of SiNP and explore its reproductive toxicity and pathogenic mechanisms. First, we coupled FITC onto SiNPs and intratracheally instilled them into pregnant mice on the fifth gestational day, and the toxic effect of SiNP was evaluated in vitro and in vivo . It was found that SiNP penetrated the trophoblast membrane, leading to apoptosis and suppression of cell proliferation, tube formation, and invasion in a dose-dependent manner. Mechanistically, SiNP dysregulated the expression of Scd1, Slc27a1, and Cpt1a, and induced over synthesis and efflux obstruction of fatty acid through the PPARγ signaling pathway. The downregulation of Caspase-3 triggered apoptosis of trophoblast, which was causally associated with intracellular fatty acid accumulation as revealed by the correlation analysis. Besides, SiNP induced uterine inflammation in vivo, which aggravated with the observation prolongation within 24 h. Overall, SiNPs were visualized by coupling with FITC, and the uterine accumulation of SiNP induced fatty acid metabolic disorder, biological dysfunction, and trophoblast apoptosis, which were mediated in part by the PPARγ signaling pathway. These findings would contribute to understanding the environmental impacts of SiNP better, as well as the development of control measures for environmental pollution.